What are the protocols and resources for sport-related concussion among top National Collegiate Athletic Association football programs? A cross-sectional survey of A5 schools - Clugston, J. R.; Diemer, K.; Chrabaszcz, S. L.; Long, C. C.; Jo, J.; Terry, D. P.; Zuckerman, S. L.; Fitch, R. W. (Clinical Journal of Sport Medicine, 2025)
Objective This study summarizes findings from a cross-sectional survey conducted among National Collegiate Athletic Association (NCAA) Division 1 football programs, focusing on sport-related concussion (SRC) protocols for the 2018 season.